2015
DOI: 10.1055/s-0035-1564254
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Recovery Following Resistance Exercise Leading or not to Failure

Abstract: This study analyzed the time course of recovery following 2 resistance exercise protocols differing in level of effort: maximum (to failure) vs. half-maximum number of repetitions per set. 9 males performed 3 sets of 4 vs. 8 repetitions with their 80% 1RM load, 3?4(8) vs. 3?8(8), in the bench press and squat. Several time-points from 24?h pre- to 48?h post-exercise were established to assess the mechanical (countermovement jump height, CMJ; velocity against the 1?m?s?1 load, V1-load), biochemical (testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
122
4
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(148 citation statements)
references
References 45 publications
14
122
4
8
Order By: Relevance
“…2). This is an interesting and practical finding because by monitoring repetition velocity during RT one can estimate, with considerable precision, how many repetitions are left in reserve in a given exercise set (which corresponds to the concept of 'level of effort' [8,10,18,23]). In Study II we also found that the percentage of performed repetitions for a given magnitude of MPV loss, against a 60 % 1RM load, showed a high absolute reliability (▶ table 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This is an interesting and practical finding because by monitoring repetition velocity during RT one can estimate, with considerable precision, how many repetitions are left in reserve in a given exercise set (which corresponds to the concept of 'level of effort' [8,10,18,23]). In Study II we also found that the percentage of performed repetitions for a given magnitude of MPV loss, against a 60 % 1RM load, showed a high absolute reliability (▶ table 6).…”
Section: Discussionmentioning
confidence: 99%
“…During RT in isoinertial conditions, and assuming every repetition is performed with maximal voluntary effort, an unintentional decrease in force, velocity and hence power output is observed as fatigue develops and the number of repetitions approaches failure [15,19,23]. Recent research has shown that monitoring repetition velocity is an objective, practical and non-invasive indicator of the acute metabolic stress, hormonal response and mechanical fatigue induced by RT [10,[18][19][20]23]. Repe tition velocity has shown a very similar pattern of decrease during a single set to failure for loads ranging from 60 % to 75 % [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel finding which has important practical applications for the prescription and monitoring of training load in resistance exercise 10 34 . Thus, a velocity-based resistance training (VBRT) approach has been successfully implemented in several studies to monitor training loads 9 11 12 28 29 30 32 or to provide a non-invasive and objective measure to quantify the neuromuscular fatigue induced by resistance exercise 13 24 25 29 30 34 . The load-velocity relationship of the deep or full squat has been reported in 2 studies 4 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, o que se observa, na prática, é a realização predominante de protocolos de treinamento com um número submáximo de repetições. Alguns estudos compararam os efeitos de protocolos com diferentes "níveis de esforço" (Gonzalez-Badillo et al, 2016;Sanchez-Medina & Gonzalez-Badillo, 2011). Esses estudos compararam protocolos de repetições máximas com protocolos submáximos, ou seja, que tiveram o número de repetições determinado em relação ao número máximo que poderia ser realizado com uma determinada intensidade, até a falha muscular.…”
Section: Introductionunclassified
“…Esses estudos compararam protocolos de repetições máximas com protocolos submáximos, ou seja, que tiveram o número de repetições determinado em relação ao número máximo que poderia ser realizado com uma determinada intensidade, até a falha muscular. Gonzalez-Badillo et al (2016) investigaram alterações geradas nos sistemas neuromuscular, endócrino e cardiovascular em protocolo composto por repetições máximas e em protocolo composto pela metade do número máximo de repetições previsto. Contudo, os próprios autores questionam se realizar metade do número de repetições seria um estímulo suficiente para obter ganhos de força e adaptações neuromusculares necessários para aumentar o desempenho esportivo.…”
Section: Introductionunclassified